AGE AS FACTOR IN THE CHANGE OF THE POSITION IN IMPACTED MAXILLARY CANINE - Stojanova, Liljana; Pavlovska, Irina; Taushanova, Biljana; Jankulovska, Mira (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
Background: Many studies have shown that mesiodistal position of impacted maxillary canine (IMC) gives the best prediction values for orthodontic treatment, or, the closer the impacted canine lies to midline, the poorer is the prognosis for orthodontic alignment. Aim: The aim of the present study is to classify IMC according to canine crown horizontal overlap with lateral or central incisor's root; to find their correlation with the age of patients with IMC. Materials and methods: A cross-sectional survey was carried out in 104 patients with IMC who attended several polyclinics and dental ordinations in north-east part of North Macedonia. Patients’ dental records as well as their panoramic radiographs were examined. We used a sector classification by Alesandri et al. Results: Dominant position of the impacted canines cusps in younger group (from 10-15 years of age), is when it is overlapping with half and a whole width of lateral incisor's root 9 (28,13%) and 17 (53,13%)), consequently. Dominant position in older group (from 15-69 years of age), is when it is overlapping a half and the whole width of central incisor's root 10 (20,41%) and 20 (40,82%), consequently (p=0,00025 sig.). Conclusion : Early detection of impacted canines and timely start of orthodontic treatment is crucial for successful treatment.